Adequacy of the ultra-short-term HRV to assess adaptive processes in youth female basketball players - Nakamura, F. Y.; Pereira, L. A.; Cal Abad, C. C.; Cruz, I. F.; Flatt, A. A.; Esco, M. R.; Loturco, I. (Journal of Human Kinetics, 2017)
Heart rate variability has been widely used to monitor athletes` cardiac autonomic control changes induced by training and competition, and recently shorter recording times have been sought to improve its practicality. The aim of this study was to test the agreement between the (ultra-short-term) natural log of the root-mean-square difference of successive normal RR intervals (lnRMSSD - measured in only 1 min post-1 min stabilization) and the criterion lnRMSSD (measured in the last 5 min out of 10 min of recording) in young female basketball players. Furthermore, the correlation between training induced delta change in the ultra-short-term lnRMSSD and the criterion lnRMSSD was calculated. Seventeen players were assessed at rest pre- and post-eight weeks of training. Trivial effect sizes (-0.03 in the pre- and 0.10 in the post- treatment) were found in the comparison between the ultra-short-term lnRMSSD (3.29 ± 0.45 and 3.49 ± 0.35 ms, in the pre- and post-, respectively) and the criterion lnRMSSD (3.30 ± 0.40 and 3.45 ± 0.41 ms, in the pre- and post-, respectively) (intraclass correlation coefficient = 0.95 and 0.93). In both cases, the response to training was significant, with Pearson`s correlation of 0.82 between the delta changes of the ultra-short-term lnRMSSD and the criterion lnRMSSD. In conclusion, the lnRMSSD can be calculated within only 2 min of data acquisition (the 1st min discarded) in young female basketball players, with the ultra-short-term measure presenting similar sensitivity to training effects as the standard criterion measure.